A pulse‐width adjustable electro‐optic Q‐switched nanosecond laser oscillator. Issue 12 (23rd August 2021) - Zhao, Chen; Bai, Zhenxu; Chen, Yifu; Qi, Yaoyao; Ding, Jie; Li, Sensen; Yan, Xiusheng; Wang, Yulei; Lu, Zhiwei
Abstract: An all‐solid‐state pulse width adjustable Nd:YAG nanosecond laser at 1064 nm is demonstrated based on the bidirectional voltage supplied Q‐switched technology. Continuously adjustable pulse‐width from 4.6 to 32.3 ns is generated in a linear cavity, which is laser diode side‐pumped at 808 nm at 100 Hz repetition rate. With 27 ns Q‐switch duration, the shortest pulse width of 4.6 ns with single pulse energy of 0.77 mJ and a near‐Gaussian beam quality ( M 2  < 1.6) is obtained. Our results suggest an approach to generating pulse‐width adjustable nanosecond lasers for applications in LIDAR.